2020
DOI: 10.3390/earth2010001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Greenhouse Gas (GHG) Emissions in the Transportation Sector of Senegal

Abstract: The transportation sector of Senegal is dominated by the road subsector, which relies on fossil fuels: gasoline and diesel. Their combustion generates substances such as carbon dioxide, methane, nitrous oxide, and many others responsible for climate change, which has negative impacts on the environment, human health, and activities. This study is based on data collected from Senegal’s official reports on transport and energy, and Intergovernmental Panel on Climate Change (IPCC) greenhouse gases’ analysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Also, it is a major contributor to human-induced climate change. It is reported that greenhouse gas emissions have grown globally at a faster rate in the transportation sector than in any other sector (Tchanche 2021 ). Logistical and transportation activities have numerous detrimental effects on the societal and natural environment which are necessary to be reduced.…”
Section: Emerging Research Themes Of Ai and Supply Chain Resiliencymentioning
confidence: 99%
“…Also, it is a major contributor to human-induced climate change. It is reported that greenhouse gas emissions have grown globally at a faster rate in the transportation sector than in any other sector (Tchanche 2021 ). Logistical and transportation activities have numerous detrimental effects on the societal and natural environment which are necessary to be reduced.…”
Section: Emerging Research Themes Of Ai and Supply Chain Resiliencymentioning
confidence: 99%
“…Many adverse consequences like greenhouse gas emissions, air pollution and noise pollution are associated with transportation-a major contributor to global greenhouse gases (Tchanche, 2021). Transportation has long-lasting and significant impacts on society, the economy and the environment, but it is a crucial element of urban sustainability (Haghshenas & Vaziri, 2012) P6.…”
Section: Sustainable Transportationmentioning
confidence: 99%
“…Specifically, here we examine how the efficacy of a reduction in miles driven by each motor vehicle each month, and a transition to alternate fuel sources, would compare to various geoengineering techniques. We select the ground transportation industry as an example of an individual action because: The transportation sector is one of the largest contributors to greenhouse gas emissions (16% of global emissions in 2016) with ground transportation making up approximately three quarters of this (Ritchie, 2020) and potentially being the easiest to manipulate (Mazur et al., 2018). The impacts of reduced driving have become apparent to the lay public during the COVID‐19 pandemic, thus providing popularized evidence of the importance of this solution to meeting climate goals (Cruickshank, 2020; Jaramillo, 2020; Simon, 2020).…”
Section: Overview Of Geoengineeringmentioning
confidence: 99%
“…The transportation sector is one of the largest contributors to greenhouse gas emissions (16% of global emissions in 2016) with ground transportation making up approximately three quarters of this (Ritchie, 2020) and potentially being the easiest to manipulate (Mazur et al., 2018).…”
Section: Overview Of Geoengineeringmentioning
confidence: 99%